Multiuser motion recognition system using smartphone LED luminescence - Oh, Byung-Hun; Kim, Jung-Hyun; Chung, Kwang-Woo; Hong, Kwang-Sook (Electronics letters, 2015)
A novel multiuser motion recognition system that uses a smartphone detection method and tracking interface is proposed. This multiuser motion recognition system provides a motion control interface between devices using an image-based object tracking algorithm through smartphone light-emitting diode (LED) luminescence. It requires just a universal serial bus (USB) camera and personal smartphone instead of expensive equipment to provide a motion control interface. It recognises the user's gestures by tracking three-dimensional (3D) distance and the rotation angle of the smartphone, which acts essentially as a controller in the user's hand.